CHD8 suppression impacts on histone H3 lysine 36 trimethylation and alters RNA alternative splicing. Issue 22 (20th December 2022) - Kerschbamer, Emanuela; Arnoldi, Michele; Tripathi, Takshashila; Pellegrini, Miguel; Maturi, Samuele; Erdin, Serkan; Salviato, Elisa; Di Leva, Francesca; Sebestyén, Endre; Dassi, Erik; Zarantonello, Giulia; Benelli, Matteo; et al.
Abstract: Disruptive mutations in the chromodomain helicase DNA-binding protein 8 gene ( CHD8 ) have been recurrently associated with autism spectrum disorders (ASDs). Here we investigated how chromatin reacts to CHD8 suppression by analyzing a panel of histone modifications in induced pluripotent stem cell-derived neural progenitors. CHD8 suppression led to significant reduction (47.82%) in histone H3K36me3 peaks at gene bodies, particularly impacting on transcriptional elongation chromatin states. H3K36me3 reduction specifically affects highly expressed, CHD8-bound genes and correlates with altered alternative splicing patterns of 462 genes implicated in 'regulation of RNA splicing' and 'mRNA catabolic process'. Mass spectrometry analysis uncovered a novel interaction between CHD8 and the splicing regulator heterogeneous nuclear ribonucleoprotein L (hnRNPL), providing the first mechanistic insights to explain the CHD8 suppression-derived splicing phenotype, partly implicating SETD2, a H3K36me3 methyltransferase. In summary, our results point toward broad molecular consequences of CHD8 suppression, entailing altered histone deposition/maintenance and RNA processing regulation as important regulatory processes in ASD.